IRF5 rs2004640-T allele, the new genetic factor for systemic lupus erythematosus, is not associated with rheumatoid arthritis. Issue 6 (7th December 2006) - Garnier, Sophie; Dieudé, Philippe; Michou, Laetitia; Barbet, Sandra; Tan, Alice; Lasbleiz, Sandra; Bardin, Thomas; Prum, Bernard; Cornélis, François
Abstract : Background: Recently, a new genetic factor within the interferon regulatory factor 5 ( IRF5 ) gene was demonstrated for systemic lupus erythematosus (SLE) through linkage and association: the rs2004640-T allele. IRF5 is involved in the production of rheumatoid arthritis (RA) cytokines, and SLE already shares with RA one genetic factor within the tyrosine phosphatase PTPN22 gene. Aim: To test the hypothesis that the SLE IRF5 genetic factor could also be shared with RA. Patients and methods: 100 French Caucasian trio families with RA were genotyped and analysed with the transmission disequilibrium test, the frequency comparison of the transmitted and untransmitted alleles, and the genotype relative risk. 97% power was available to detect at least a trend in favour of a factor similar to that reported for SLE. Results: The analysis showed the absence of linkage and association globally and in "autoimmune" RA subsets, with a weak non-significant trend against the IRF5 rs20046470-T allele. Given the robustness of familial-based analysis, this slight negative trend provided strong evidence against even a weaker factor than that reported for SLE. Conclusion: Our results exclude the IRF5 rs2004640-T allele as a major genetic factor for RA in this French Caucasian population.